2021
DOI: 10.17755/esosder.734518
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Dönem Çocuklarinin Sosyal Beceri̇ Düzeyleri̇ni̇n Anneleri̇ni̇n Empati̇ Beceri̇leri̇ İle İli̇şki̇si̇

Abstract: Bu araştırma, çocukların sosyal becerileri üzerinde yaş ve cinsiyet; annelerin empatik becerileri üzerinde yaş, öğrenim düzeyi ve çalışma durumu gibi değişkenlerin anlamlı bir farklılık oluşturup oluşturmadığının incelenmesi ve çocukların sosyal becerileri ile annelerin empatik becerileri arasındaki ilişkinin incelenmesi amacıyla yapılmıştır. Bu amaç doğrultusunda araştırma, Şanlıurfa ili Suruç ilçesindeki resmi bağımsız anaokulları ile resmi ilköğretim okullarının anasınıflarına giden 103 çocuk ve annesi ile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…However, no significant difference was found based on gender in terms of personal care skills 38 . In another study, the scores obtained from the "Social Skills Scale Based on Gender" indicated that female children (43.65) managed their emotions better than male children (39.26), supporting the idea of gender-related differences in social skills 39 . In our study, 29.9% of female children demonstrated advanced social skills and self-care development, while 19.0% of male children exhibited advanced development.…”
Section: Discussionmentioning
confidence: 84%
“…However, no significant difference was found based on gender in terms of personal care skills 38 . In another study, the scores obtained from the "Social Skills Scale Based on Gender" indicated that female children (43.65) managed their emotions better than male children (39.26), supporting the idea of gender-related differences in social skills 39 . In our study, 29.9% of female children demonstrated advanced social skills and self-care development, while 19.0% of male children exhibited advanced development.…”
Section: Discussionmentioning
confidence: 84%
“…Social skills include establishing positive relationships with peers, considering the norms of the social environment, protecting others' rights, respecting others' feelings, gaining a sense of belonging to society, adopting society's value judgments, taking responsibility, and being loved and respected by others (Çubukçu & Gültekin, 2006). There is a breadth of studies on these social skill variables in early childhood (Atmaca et al, 2021;Başar, 2013;Can-Yaşar, 2011;Demiriz & Dinçer, 2000;Gizir & Baran, 2003;Gülay, 2011;Gültekin-Akduman et al, 2015;Kandır & Alpan, 2008;Koçak & Tepeli, 2006;Orçan & Deniz, 2006;Özbey, 2012;Tanrıverdi & Erarslan, 2015). Social competence, defined as the ability to establish close relationships with others, is a phenomenon influenced by the relationships among sociocultural contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Çocuğun en yakın çevresi ve en önemli ilişkileri ana-babasıyla olan ilişkidir ve bu ilişkinin sağlıklı olması çocuğun çevresine uyum gösterebilmesinde önemlidir (Günalp, 2007). Öyle ki kalıtımsal ya da çevresel birçok etken çocuğun hayata ve kendisine karşı bakışını etkilemekte uyumlu, uyumsuz birçok davranışın oluşmasına sebep olmaktadır (Aslan, 1992;Atmaca, Gültekin-Akduman & Şepitci-Sarıbaş, 2021;Çağdaş & Seçer, 2006;Oğuz, 2006).…”
Section: Introductionunclassified